Structural basis of human PCNA sliding on DNA - Matteo De March (Nature Portfolio, 2017)
DNA sliding clamps are ring-shaped proteins that encircle DNA and harbour polymerases and other factors that promote processive DNA replication. Here the authors use X-ray crystallography, NMR and MD simulations to propose a model for a PCNA sliding mechanism that relies on short-lived polar interactions.